Enhancing English Speaking Proficiency Of Batik And Textile Creative Crafts Students Of Smkn 6 Jember Through Public Speaking - Pramudita, Rizqi Febrian; Wicaksono , Julien Arief; Kamal , Mushthofa; Suharsono , Degita Danur; Taufan , Gullit Tornado (Journal Of Humanities Community Empowerment, 2024)
Partners were trying to explore their potential by preparing several students to become their ambassadors. Due to students’ lack of confidence especially in communicating using English, their plans could not execute well. This program aims to enhance the English-speaking proficiency of students at SMKN 6 Jember. It is conducted for 4 weeks involving 18 selected students of Batik and Textile Creative Crafts Major. The method used Public Speaking with an interpersonal communication approach, which is divided into two stages namely early public speaking training and main public speaking training. The result of this program is students can communicate using English, especially in describing batik and textile creative crafts at school.